Size effect of circular concrete‐filled stainless steel tubular short columns under axial compression. (8th November 2022) - Liu, Xiaolong; Wang, Senping; Yuan, Bo
Summary: Concrete‐filled stainless steel tube (CFSST) members combine the advantages of stainless steel materials and concrete‐filled steel tube (CFST) members. Therefore, it has a broad range of applications than CFST members in the marine environment and other scenarios requiring great durability and corrosion resistance. However, there are limited researches on the large‐sized CFSST members. In this paper, 30 circular CFSST members with varying steel ratios (3.7% ≤  α  ≤ 10.3%), diameters (500 mm ≤  D  ≤ 900 mm), and strength of concrete ( f cu = 40 MPa, 50 MPa) are studied on the size effect under axial compression. For peak axial stress, peak axial strain, and composite elastic modulus, size effects are investigated. According to the results, the peak axial stress and peak axial strain of the members increase with the increase in diameter. The modulus of composite elasticity essentially stays constant as the diameter increases, showing that there is no obvious size effect on the composite elastic modulus. The size effect of peak axial stress and peak axial strain is influenced by the steel ratio. Increasing the steel ratio tended to decrease the size effect. According to the generated data, it was found that the current codes of Chinese and European underestimate the ultimate bearing capacity of CFSST short columns significantly. To this end, the resistances of the large‐sized austenitic CFSST columns with a low steel ratio are well predicted by the proposed design model after being modified, based on GB 50936‐2014 and EN 1994‐1‐1 design codes.